Body-worn cameras: An effective or cosmetic policing response to domestic and family violence? - Pfitzner, Naomi (Criminology & criminal justice, 2023)
Drawing together the literature on police body-worn cameras and video-recorded evidence in domestic and family violence matters, this article explores whether technology can ‘fix’ criminal justice responses to domestic and family violence. We argue that the use of police body-worn cameras and digitally recorded audio-visual evidence in domestic and family violence matters is not a cure-all for deficiencies in criminal justice responses to domestic and family violence. While the use of such technologies may alleviate some of the deficiencies highlighted in the Australian state of Victoria’s 2016 Royal Commission into Family Violence, it raises serious concerns about victim’s agency and privacy. We argue that the introduction of such technologies requires significant investment in training and education – for police to adapt to their changed role and for judicial officers, legal practitioners and potential jurors in understanding and interpreting victim survivor behaviour on film.